Development of an Android-Based CT Scan Examination Scheduling Information System at The Radiology Installation of Dr. H. Abdul Moeloek Hospital, Lampung Province - Dinar Scicilia Kusmasyri; Sudiyono Sudiyono; Darmini Darmini (International Journal Labs, 2025)
The information system for scheduling CT scan examination with contrast at RSUD dr. H. Abdul Moeloek still uses a manual system by recording in the CT scan examination agreement logbook. This system causes inefficiency, delays in service and a high risk of errors. Therefore, it is necessary to develop an android-based system that is easily accessible and used by medical and administrative staff so that the quality of radiology services is improved. Objective To design and develop an android-based CT Scan examination scheduling information system at RSUD dr. H. Abdul Moeloek Lampung Province, test the feasibility or validation of the scheduling information system development and analyse the effectiveness of the development of an android-based CT Scan examination scheduling information system at RSUD dr. H. Abdul Moeloek Lampung Province. The method used is Research and Development (R&D). Expert validity test is guided by ISO 9126. The effectiveness test includes resource efficiency, time, cost, and service quality. The developed system is called ‘SIPEDE CT Scan’. The results of the expert validity test based on ISO 9126 guidelines were 98.95% with very good criteria. The Asymp.Sig (2-tailed) effectiveness test result is 0.001 (<0.05), meaning that it can be said that there is an effect of using the CT Scan scheduling information system with android-based contrast on resources, time, costs and service quality. This study resulted in the development of an android-based CT Scan scheduling information system that is more effective and can improve service quality.